Medical Therapy in Idiopathic Pulmonary Fibrosis - Antoniou, Katerina M.; Wuyts, Wim; Wijsenbeek, Marlies; Wells, Athol U. (Seminars in Respiratory and Critical Care Medicine, 2016)
Medical therapy for idiopathic fibrosis remains controversial. Idiopathic pulmonary fibrosis (IPF) was uniformly a disease that progressed inexorably, typically leading to death within 3 to 5 years from onset of symptoms. Until recently, lung transplantation was the only effective transplant option. Within the past decade, several placebo-controlled trials failed to show benefit in patients with IPF. However, within the past 2 years, two novel antifibrotic agents (pirfenidone and nintedanib) were approved by the Food and Drug Administration (FDA) in the United States and European Medicines Agency (EMA) based upon pivotal studies that showed benefit (specifically slowing of the rate of disease progression) with both agents. Short-term outcomes (12 months) showed less deterioration of physiological parameters (e.g., change in forced vital capacity), although survival benefit has not convincingly been established with either agent. Nonetheless, these agents bring a glimmer of hope to patients with this deadly disease. The appropriate indications for initiating therapy, best candidates for therapy, and possible role for combination therapy remain controversial. Additional studies using agents that attenuate or abrogate profibrotic cytokines and chemokines may provide even further improvement in the future.
Keywords: idiopathic pulmonary fibrosis; pirfenidone; nintedanib